Uniform W-182 isotope compositions in Eoarchean rocks from the Isua region, SW Greenland: The role of early silicate differentiation and missing late veneer - Tusch, J.; Sprung, P.; van de Loecht, J.; Hoffmann, J. E.; Boyd, A. J.; Rosing, M. T.; Muenker, C. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Eoarchean rocks from the Isua region in southern West Greenland are known to exhibit isotope anomalies of W-182 and Nd-142. The excess W-182 in many rocks from the Isua region have been explained by two endmember models: (1) missing late veneer or (2) silicate differentiation shortly after Earth's formation. Furthermore, it has been proposed that pristine W isotope systematics in rocks from the Isua region (herein the Isua supracrustal belt and adjacent area) have been obscured by metamorphic disturbance. To address these issues, we present a comprehensive dataset, combining high precision W-182 isotope data with trace element data, including high precision elemental W-Th-U-Ta abundance data. We present an improved analytical protocol that allows processing gram-sized samples with W abundances in the lower ng/g range. This protocol also results in markedly improved ion exchange column yields and cleaner W fractions, thereby minimizing nuclear volume effects on W-182. To compare with previous studies, our dataset includes some samples from previously investigated units in the Isua region (Isua Supracrustal Belt (ISB) mafic-ultramafic assemblages and Ameralik dikes). In addition, several Eoarchean key units in the Isukasia terrane (Isua region) and the Faeringehavn terrane (Nuuk region) have been examined for their W isotope composition in this study for the first time. These newly investigated units include recently recognized mantle-like peridotites from both terranes that display PGE abundances and patterns similar to modern depleted mantle peridotites, felsic lithologies from the ISB, as well as key amphibolite and TTG localities from low-strain domains south of the ISB. Virtually all rocks from the Isua region show significant W enrichment with W/Th of up to 160 in mafic to ultramafic samples. None of the samples from SW Greenland that were object of W-182 isotope analysis in this study and virtually all previous studies appear to have preserved near canonical W/Th ratios (i.e., between 0.09 and 0.24). ...